Magnetic Resonance Imaging versus Computed Tomography in Temporal Bone Carcinoma: Radiological and Pathological Correlation. (2nd September 2014) - Spear, Samuel A.; Mehta, Rahul; Jackson, Neal; Ying, Yu‐Lan Mary; Nuss, Daniel W.; Arriaga, Moises A.
Abstract : Objectives: Correlate the findings of preoperative magnetic resonance imaging (MRI) and computed tomography (CT) in temporal bone carcinoma with histopathological findings following lateral temporal bone resection. Methods: In this retrospective review, 11 cases of temporal bone carcinoma over the past 3 years were reviewed at our institution. Preoperative CT and MRI scans were systematically reviewed for tumor involvement in 10 anatomic areas involving and surrounding the temporal bone. These were compared with results found on final histopathology. Results: Among the 11 cases, 30 anatomic areas of tumor involvement identified on CT imaging were also found on MRI and confirmed on final histopathology. Two areas suggestive on tumor involvement on CT and MRI (parotid gland and regional lymph nodes) and 2 areas on MRI alone (mastoid antrum and middle ear) were negative on final histopathology. MRI did not change the preoperative clinical staging in any of the 11 cases, however, examination of the MRI in 1 case suggested temporal lobe involvement that was not seen on CT images and subsequently changed the management of the patient. Conclusions: The addition of MRI in the preoperative evaluation of these patients confirmed the extent of tumor involvement seen on CT and did not identify additional tumor or facial nerve involvement in most cases except for one advanced case. In this case, the addition of the MRI findings changed the treatment plan. While CT remains the imaging gold‐standard for preoperative evaluation and staging, MRI should be obtained in evaluating advanced temporal bone tumors.